Quality of life measures in health care. I: Applications and issues in assessment. Issue 6861 (31st October 1992) - Fitzpatrick, R.; Fletcher, A.; Gore, S.; Jones, D.; Spiegelhalter, D.; Cox, D.
Abstract : Many clinicians remain unsure of the relevance of measuring quality of life to their clinical practice. In health economics quality of life measures have become the standard means of assessing the results of health care interventions and, more controversially, the means of prioritising funding; but they have many other applications. This article--the first of three on measuring quality of life--reviews the instruments available and their application in screening programmes, audit, health care research, and clinical trials. Using the appropriate instrument is essential if outcome measures are to be valid and clinically meaningful.